Poznavanje in pogostost izvajanja nordijske in kopenhagenske vaje med registriranimi športniki v Sloveniji - Leban, Žiga (Šport (Ljubljana), 2022)
Nordic hamstring exercise and Copenhagen adduction exercise have been shown to reduce the incidence of hamstring injuries and groin injuries. These injuries are the most common injuries in any sport containing sprinting, sudden direction change, kicks or skating step (hockey). The purpose of this study is to evaluate the awareness and implementation of Nordic hamstring exercise and Copenhagen adduction exercise among players, coaches and therapist/physician from the best Slovenian leagues in athletics, hockey, basketball, football and tennis. Of these, 90,5 % were aware of Nordic hamstring exercise, of which 72 % were implementing in their practice, while 55,4 % athletes were aware of Copenhagen adduction exercise, of which 51,2 % were performing it. Athletes who implemented Nordic hamstring exercise reported positive attitude about program efficacy, with a score of 7,3 ± 1,5 out of 10, while Copenhagen adduction exercise got a score of 7,2 ± 1,4 out of 10. Further work must be done to educate players, coaches and therapist/physician about the importance of implementing Nordic hamstring exercise and Copenhagen adduction exercise and their effectiveness.
Keywords: kopenhagenska vaja; nordijska vaja; nordijski upogib; šport; športne poškodbe; vadba